Behavioral responses of bioluminescent fireflies to artificial light at night - Owens, Avalon C. S.; Van den Broeck, Mira; De Cock, Raphaël; Lewis, Sara M. (Frontiers in Ecology and Evolution, 2022)
Bioluminescent insects have been the subject of scientific interest and popular wonder for millennia. But in the 21st century, the fireflies, click beetles, and cave glow-worms that brighten our nights are threatened by an unprecedented competitor: anthropogenic light pollution. Artificial lights can obscure the light-based signals on which these and other bioluminescent organisms rely to court mates, deter predators, and attract prey. In the following review we summarize a recent influx of research into the behavioral consequences of artificial light at night for firefly beetles (Coleoptera: Lampyridae), which we organize into four distinct courtship signaling systems. We conclude by highlighting several opportunities for further research to advance this emerging field and by offering a set of up-to-date lighting recommendations that can help land managers and other stakeholders balance public safety and ecological sustainability.